Children's literature and reading habit - Gupta, Vijaya (New Delhi, India Deep & Deep Publications, 1997)
Study in the Indian context.
Keywords: Children's literature -- History and criticism; Children -- Books and reading; Children's literature -- Psychological aspects; Critical thinking in children; Reading -- Parent participation